Novel and rapid analytical platform development enabled by advances in 3D printing - Malinick, Alexander S.; Ebel, Cole P.; Stuart, Daniel D.; Valiulis, Santino N.; Hanson, Victor A.; Cheng, Quan (Frontiers in analytical science, 2024)
3-Dimensional (3D) printing technology has greatly facilitated the recent advancements in science and engineering that benefit many aspects of scientific investigation, with examples including disease diagnostics, dentistry, aerospace, and fundamental research. For analytical chemistry, many advancements can be directly linked to achievements associated with 3D printing of optics, flow systems, mechanical/structural components, and parts related to detection/measurement, which before the advent of 3D printing were limited by complicated, cumbersome, expensive, and material-limited production. More importantly, the totality of these advances has made the possibility of 3D printing the majority of an analytical system an achievable reality. In this review, we highlight the recent achievements and advancements reported in literature that will facilitate the development of the next-generation analytical instrumentation through the use of 3D printing technology. A great deal of attention is given to those in the context of bioanalytical platforms and novel biosensing strategies. Limited by space, we will explicitly focus the discussion on the following areas: improvement/utilization of new printing materials, methods towards higher resolution, fabrication and production of optical components, novel microfluidic flow systems, and printed structural components for instrumentation.